KIDNAPPING OF CORPORATE HUMAN RESOURCES AND BUSINESS VIABILITY: INSIGHTS FROM SOUTH-EASTERN METROPOLITAN CITIES - Njoku, Kenneth Chukwudi; Uzodimma, Emmanuel Ezenwa; Osolafia, Muhammad Egye (African Journal of Social and Behavioural Sciences, 2025)
The research evaluates the kidnapping of corporate human resources and business viability in South-Eastern Metropolitan Cities. The study examines the extent to which kidnapping affects employee retention in business enterprises in South Eastern metropolitan cities; and to assess the extent to which kidnapping affects customer engagement in business enterprises in South Eastern metropolitan cities. The research adopts the survey research design. The study uses primary sources of data. The sample size of the study is 105. A structured questionnaire was the major instrument for data collection. The study adopts the purposive sampling technique. The research uses Cronbach Alpha statistic was used to obtain the value of 0.75 as the instrument reliability ratio. Descriptive and inferential statistics were employed for data analysis. The findings reveal that there is a positive and significant extent to which kidnapping affects employee retention; there is a positive and significant extent to which kidnapping affects customer engagement in business enterprises in Southeast metropolitan cities. The study concludes that the kidnapping of corporate human resources personnel can erode business viability in business enterprises in Southeastern metropolitan cities. The study recommends, among others, that business enterprises in South Eastern metropolitan cities need to encourage their workers to be security conscious so as to improve employee retention and customer engagement.